2014
DOI: 10.1590/s0100-720320140004952
|View full text |Cite
|
Sign up to set email alerts
|

Função sexual de mulheres submetidas à reprodução assistida

Abstract: WaldeMar naves do aMaral 2 Resumo OBJETIVO: Avaliar a função sexual de mulheres submetidas a técnicas de reprodução assistida. MÉTODOS: Estudo caso-controle com 278 mulheres atendidas no Hospital das Clínicas da Universidade Federal de Goiás nos serviços de Reprodução Humana e no Ambulatório de Ginecologia. As mulheres foram distribuídas em grupo caso (168 mulheres inférteis) e grupo controle (110 mulheres férteis), e responderam ao questionário Índice de Função Sexual Feminina (IFSF) para avaliação da função … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(45 reference statements)
2
2
0
Order By: Relevance
“…The IG had a significantly lower FSFI subscore for arousal than the CG. These results are consistent with a case-control study that showed a lower score in arousal of infertile women, 27 although this study also reported that infertile women had lower scores in sexual desire.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The IG had a significantly lower FSFI subscore for arousal than the CG. These results are consistent with a case-control study that showed a lower score in arousal of infertile women, 27 although this study also reported that infertile women had lower scores in sexual desire.…”
Section: Discussionsupporting
confidence: 92%
“…However, the control group in this study was from a gynecology outpatient clinic, and this group may be prone to more sexual complaints. 5 The prevalence of sexual dysfunction in our study was similar to that in a previous case-control study 27 as well as to that of a cross-sectional study, in which 35.6% of infertile women had FSFI scores < 26.55. 28 On the other hand, another cross-sectional study found that 87.1% of the infertile women had sexual dysfunction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Prevalence data diverse, varying according to the authors and the geographic region, but Europe and North America typically had rates of FSD below 40%, whereas regions such as the Middle East and Africa had rates as high as 62% [12,13] Several factors have been associated to FSD. According to the results of a metaanalysis that includes 94 studies, and despite the heterogeneity of the population evaluated, the following factors showed to have a significant, protective effect: older age at marriage, exercise, good overall health, daily intimacy and relationship satisfaction, positive body image, sex education and finding sex to be "important" [13] Some studies have evaluated the relationship between FSD and infertility but the results remain controversial [14][15][16]. Thus, the aim of this systematic review was to provide a meta-analytical estimate of the relation between infertility and FSD.…”
Section: Introductionmentioning
confidence: 99%